WACANA RAYUAN GOMBAL SEBAGAI SALAH SATU BENTUK HUMOR - , ADINDA PUTRI P, Agustin Retnaningsih S.S., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study deal with the use of language in Wacana Rayuan Gombal (WRG). Which includes discussion of topics, semantic relation and style, and its pragmatic violation. All data presented in this study are collected from two published books and Facebook, and are analysed by using referential identity method, componential analysis, and pragmatic identity method. The result of the study shows that the WRG uses various topics such as profession, objects, figures, animals, places, hobbies, science knowledges, activities, and regional identities. From language view points, it is found that WRG use relation of meaning. Those are synonymy and hypernymy. It is found also that WRG use informal style, repetitions, hyperboles, methaphors, sarcasms, and similes. Pragmatically, the WRG is crowded with violation of cooperative and politeness principles.